Grammatical And Lexical English Collocations: Some Possible Problems To Indonesian Learners Of English - Rio Rini Diah Moehkardi (Humaniora, 2002)
It seems universally acknowledged in all languages that words often co-occur with other word(s) in units. However, they are not always freely combined nor individually analyzable. Their co-occurences are adhered to some grammatical principles. The English prepositional phrase, at the moment, for example, is subject to grammatical choice of the preposition at rather than other random prepositions like on or in. Another example, verbal phrase look forward to is followed by gerund and not infinitive. Therefore, such phrases are also called lexico-grammatical units (Nattinger and DeCarrico, 1992:8). These unit are often confusing to learners not only because of their various semantic and syntactic requirements like the above examples, but also the double-function of their elements. Many words that combined with verbs can be used as either prepositions or adverbs, for example: above, across, along, before, behind, off, on, over, etc.(Thomson and Martinet, 1980:82) The examples for consideration are: (a) He got off the bus at the corner. Off in this got off verb combination is a preposition, and (b) He got off at the corner. Off that goes with the verb got in (b) is an adverb (also called adverbial particle).The co-occurence of off following got in (a) is expressing predictable direction and therefore is not as fixed as the one following got in (b) which expresses new Martinet, 1980: 83) may also function as conjunction. It is obvious that the function of grammar in conveying meaning is not only at sentence level, but also at phrase level. This confirms what has also been suggested by Kennedy (1990:216) that to some extent collocations are considered as “grammar in terms of vocabulary.” Due to the complexity of English collocation, this paper is going to discuss the types of English collocations, their possible problems to Indonesian learners of English and some solutions.